Inhibition of malignant phenotypes of human osteosarcoma cells by a gene silencer, a pyrrole–imidazole polyamide, which targets an E‐box motif. Issue 1 (13th March 2014) - Taniguchi, Masashi; Fujiwara, Kyoko; Nakai, Yuji; Ozaki, Toshinori; Koshikawa, Nobuko; Toshio, Kojima; Kataba, Motoaki; Oguni, Asako; Matsuda, Hiroyuki; Yoshida, Yukihiro; Tokuhashi, Yasuaki; Fukuda, Noboru; et al.
Abstract : Gene amplification and/or overexpression of the transcription factor c‐MYC, which binds to the E‐box sequence (5′‐CACGTG‐3′), has been observed in many human tumors. In this study, we have designed 5 pyrrole–imidazole (PI) polyamides recognizing E‐box, and found that, among them, Myc‐6 significantly suppresses malignant phenotypes of human osteosarcoma MG63 cells both in vitro and in vivo. Intriguingly, knockdown of the putative Myc‐6 target MALAT1 encoding long noncoding RNA remarkably impaired cell growth of MG63 cells. Collectively, our present findings strongly suggest that Myc‐6 exerts its tumor‐suppressive ability at least in part through the specific down‐regulation of MALAT1 . Abstract : We generated pyrrole–imidazole (PI) polyamides that could bind to an E‐box motif. PI polyamide Myc‐6 induces G1 arrest and apoptosis in human osteosarcoma MG63 cells. Myc‐6 represses tumor growth both in vitro and in vivo. Myc‐6 binds to the 5′‐upstream region of noncoding RNA MALAT1 and reduces its expression. Myc‐6 exerts its tumor‐suppressive ability through the down‐regulation of MALAT1 .